An Efficient, New, Simple and Rapid Method for Synthesis and Isomerization of Heteropolyanion B-[PW9O34]9- - Sharifzadeh Baei, M.; A. Rezvani, M. (Asian Journal of Chemistry, 2011)
In this article, microwave assisted synthesis of B-PW9O34 9- is investigated. This new method is an efficient, simple and green procedure for synthesis and isomerization of B-PW9O34 9- heteropolyanion under microwave irradiation. The reaction carried out using the microwave method possessed shorter reaction times and higher yields than the thermal method. The product was characterized by IR, XRD and cyclic voltammetric spectroscopy and compared with references. It has been established that the B-PW9 isomer is formed from the deformation of A-PW9 by a thermal process. This anion (B-PW9) is unstable in aqueous solution and converts to the thermodynamically more stable A-PW9, unless it is reacted with a transition metal cation. There are large numbers of equilibria among several different species in the solutions of polyoxometalates.